Kewajiban Pemimpin Menurut Susastra Hindu - Putu Sanjaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The ability to control oneself is something everyone should do even more so that he is a leader. Leaders who are able to control themselves will be more able to carry out and carry out their duties in the lead and will be more able to create a safe life, peace and peace to the community he leads. One of the self-controls a leader must perform is to control craving, anger, greed, drunkenness, arrogance and pride in him. In Hindu texts or literature, such matters have been clearly and explicitly stated and mandated. Texts such as Arthasastra and Sarasamuccaya clearly contain teachings about self-control. Through this paper, with literary and descriptive approaches, the teachings of leadership in Hindu literature, especially Arthasastra and Sarasamuccaya are put forward.Keywords: Obligations, Leader, Literature, Hinduism